Controlling Automated Manufacturing Systems
112 p.
Keywords: Master production scheduling II 60 On-line scheduling 65 Specific data requirements 69 Mailbox approaches 70 Conclusion 72 Chapter 7: Cell Level Control 75 Introduction 75 CCS classification 77 What is a cell? 78 CCS operational modes 80 Conclusion 86 Chapter 8: Equipment Level Control 89 Introduction 89 What is meant by equipment? 90 Equipment level control structure 92 Conclusion 94 Chapter 9: Conclusion and Future Trends 95 Overall production planning and control functions 98 Future trends 100 Conclusion 102 Appendix I: Master Production Scheduling II 103 References 107 Index 109 Preface This book is intended as an introduction to production planning and control of automated manufacturing systems. As such, it links together two diverse fields of interest: in the area of production planning and control there is a large body of work completed in analytical models, computer structures and overall systems; equally, for the hardware and detailed control aspects of the equipment used (for example, NC machines, robots, etc), comprehensive studies have also been completed. To cover each area fully would result in a work of several volumes. Instead, this book stresses the important elements of both areas that are vital to effective production planning and control of the whole automated manufacturing system.